Redesigning Ergonomic Vertical Folding Desk in an Apartment Room using Anthropometric Approach - Handoyo; Wiraputra, Anindyo Fikri (Future Science)
The use of a desk is generally big and can only be used for learning and does not have any additional functions; it causes the table to consume a lot of space in a room. The occupancy of the vertical occupancy is minimal, given the numerous availability. This design hopes to meet the needs of users who live in a place with narrow areas such as apartments, boards, houses, and other living rooms to do some activities related to the function of furniture that will be designed. With the increasing interest of people living in apartments, it is essential to consider furniture that will be used in a relatively narrow room. Thus, it is needed to overcome the conditions of the confined room. This research aims at redesigning an ergonomic and innovative folding desk in the apartment room, to provide comfort in its users. In improving the folding desk, it is hoped that this proposed folding desk will be more ergonomic and can be used daily. The results show that the recommended size for the ergonomic desk is 62 cm wide, 163 cm long, and 29 cm high; also, the recommended size of the seat is 50 cm high.